PENGARUH LINGKUNGAN KERJA PSIKOSOSIAL DAN KONTROL DIRI TERHADAP PROKRASTINASI KERJA PADA SALES PERSON PT.X - Arum Pandan Sari (Universitas Pahlawan Tuanku Tambusai, 2022)
Sales person is a major thing in sales, Work procrastination is something that companies really avoid, mainly doing by sales people. Work procrastination done by sales person is influenced by several factors, one of the factors within the individual is self-control. External factors are the psychosocial work environment. This study aims to examine the effect of the psychosocial work environment and self-control on work procrastination in sales persons at PT.X. The sampling technique used simple random sampling technique with a total sample of 77 sales persons. Data analysis used multiple regression techniques. The results showed that there was an influence of the psychosocial work environment and self-control separately or together on work procrastination in sales persons at PT.X. The joint analysis shows a coefficient of F value of 14,784 and a significance coefficient of 0.000 (p ≤ 0.05) and an R square of 0.285 is obtained. This means that there is a very significant influence between the psychosocial work environment and self-control together on work procrastination in sales persons at PT.X with a relative contribution of 28.5% while the remaining 71.5% is influenced by other factors. not included in this study. Keywords : Psychosocial Work Environment, Self-Control, Work Procrastination, Sales Person.